2015
DOI: 10.1038/srep14689
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic effects on a tropical forest according to the distance from human settlements

Abstract: The protection of tropical forests is one of the most urgent issues in conservation biology because of the rapid deforestation that has occurred over the last 50 years. Even in protected forests, the anthropogenic effects from newly expanding villages such as harvesting of medicinal plants, pasturing cattle and forest fires can induce environmental modifications, especially on the forest floor. We evaluated the anthropogenic effects of the daily activities of neighboring residents on natural forests in 12 plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…For example, Top et al [35,36] showed that higher population density and shorter distance to villages led to more forest degradation in Cambodia. Popradit et al [37] indicated forest stocks and biodiversity were reduced with decreasing distance to villages in Thailand. In our study, five variables (elevation, slope, and distance to market, to village, and to CF boundary) were likely to be related to forest accessibility, and these all were negatively related to the probability of deforestation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Top et al [35,36] showed that higher population density and shorter distance to villages led to more forest degradation in Cambodia. Popradit et al [37] indicated forest stocks and biodiversity were reduced with decreasing distance to villages in Thailand. In our study, five variables (elevation, slope, and distance to market, to village, and to CF boundary) were likely to be related to forest accessibility, and these all were negatively related to the probability of deforestation.…”
Section: Resultsmentioning
confidence: 99%
“…Fragment size was included considering that larger vegetation patches can accommodate a larger number of individuals, species and ecological interactions, thus mimicking the conditions found in undisturbed habitats (Collins et al 2017). The distance from each fragment to the closest village was included assuming that fragments in close proximity to human settlements are exposed to greater disturbance (e. g., logging and resource extraction, magnification of the edge effect; Popradit et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…This study deliberately focused on this region in order to gather knowledge on the extent of land cover change as this also directly or indirectly influences changes in the entire water tower's ecosystem over time. This region is considered to have intense and dynamic human activities [69]. The 5 km buffer zone covers an area of 415,802 ha.…”
Section: Land Cover Change In Mau Water Tower 1986-2015mentioning
confidence: 99%